2021
DOI: 10.1002/mgg3.1810
|View full text |Cite
|
Sign up to set email alerts
|

Deep analysis of the LRTOMTc.242G>A variant in non‐syndromic hearing loss North African patients and the Berber population: Implications for genetic diagnosis and genealogical studies

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In one sibling (DF549-1 and 2) with WS2 (HI associated with iris heterochromia), no mutations in WS-associated genes have been detected, however, a homozygous missense variant c.242G>A; p.(Arg81Gln) has been identified in exon 7 of the LRTOMT gene. This is a founder mutation frequently associated with non-syndromic HI (DFNB63) in North Africa (Tunisia, Morocco, Libya) ( Ahmed et al, 2008 ; Charif et al, 2012 ; Mosrati et al, 2021 ; Souissi et al, 2021 ). To date, the LRTOMT gene has not been associated with a syndromic clinical entity.…”
Section: Resultsmentioning
confidence: 99%
“…In one sibling (DF549-1 and 2) with WS2 (HI associated with iris heterochromia), no mutations in WS-associated genes have been detected, however, a homozygous missense variant c.242G>A; p.(Arg81Gln) has been identified in exon 7 of the LRTOMT gene. This is a founder mutation frequently associated with non-syndromic HI (DFNB63) in North Africa (Tunisia, Morocco, Libya) ( Ahmed et al, 2008 ; Charif et al, 2012 ; Mosrati et al, 2021 ; Souissi et al, 2021 ). To date, the LRTOMT gene has not been associated with a syndromic clinical entity.…”
Section: Resultsmentioning
confidence: 99%
“…Close to p.Leu60Pro variant, various changes in the same exon 7 were also associated with cases of moderate to profound congenital deafness making of this segment a mutation hot spot in the LRTOMT gene [10]. Besides the above homozygous c.242G>A (p.Arg81Gln) variant found in Tunisian, Libyan and Egyptian families [9,20] we may also cite missense variants c.122G>A (p.Arg41Gln), c.193T>C (p.Trp65Arg) in Morocco and Tunisia [11,12] and a nonsense mutation c.208C>T (p.Arg70*), in Tunisia [11,12,13] (Table 1). In this ethnic context, we noticed that all four affected families carrying the LRTOMT mutation (c.179T>C;p.(Leu60Pro) identified in this report belonged to the Moors (Maures), a predominant racial group of the Mauritanian population.…”
Section: Discussionmentioning
confidence: 94%
“…The wild type leucine residue was also located in an evolutionary highly conserved region [12] suggesting an important functional position of the residue (Fig 1B). Modeling, using WHATIF server (http://swift.cmbi.ru.nl) on rat COMT crystal structure as template for catechol-Omethyltransferase domain of the human LRTOMT2 (NM_001145309.4) showed that common LRTOMT variants associated with non-syndromic recessive hearing impairment led to hair cell degeneration process [9,11,20]. Close to p.Leu60Pro variant, various changes in the same exon 7 were also associated with cases of moderate to profound congenital deafness making of this segment a mutation hot spot in the LRTOMT gene [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations